Manuscript Mystique: 𝔓72 a Canon of Petrine Authority for a Proto-Orthodox “Community”? - Oliveira, Nycholas L. D. (Religion & theology, 2024)
The following study takes its cue from a body of literature that seeks to challenge the academic discourse on “religion” as transcendent, irreducible, and unique – sui generis. Naturally, a sui generis conception of religion also views religion’s objects through a lens of transcendence and divine authority. These objects possess immense meaning potential and act as social mediators in particular social contexts. In both ancient and modern times, early Christian manuscripts are examples of such religious objects. They are evidence of the literary practices of early Christians and are windows into their social contexts, reflecting how these believers navigated their socio-cultural realities. Modern scholars often use these manuscripts as evidence to postulate the existence of homogeneous Christian communities who created these texts for their theological upliftment. However, are such postulations supported by the material evidence? This paper examines one case study where 𝔓72 has been propped up as a witness to the presence of a coherent unified proto-orthodox Christian community in the fourth century CE in Egypt. The following research concludes that extant evidence points to a socio-religious context in Egypt during this period that was remarkably complex; as such, the existence of such a community cannot be supported.